Export destination and firm upgrading: Evidence from Spain - Akin A. Cilekoglu (Journal of Applied Economics, 2024)
This paper examines the role of export destinations on firm upgrading. I exploit the real effective exchange rate devaluation in Spain during the Great Recession to identify the unusual export performance of manufacturing firms. Using directly observable measures of firm upgrading, I find that increased share of exports to low-income destinations in sales reduced productivity and upgrading efforts of firms. However, real effective exchange rate devaluation did not affect the share of exports to high-income destinations in sales as well as productivity and upgrading efforts. The results are consistent with the quality sorting hypothesis that suggests a positive relationship between firm productivity and product quality. The findings in this paper emphasize that export market destination is an important determinant in analysing the gains from exporting.
Keywords: 330; exchange rate; Exports; firm upgrading; market destination